2021
DOI: 10.1136/tsaco-2021-000749
|View full text |Cite
|
Sign up to set email alerts
|

Urine drug screen positive for cocaine and amphetamine is not an adverse risk factor for cardiovascular morbidity or mortality in trauma

Abstract: BackgroundUrine drug screening (UDS) is a component of trauma workup and of perioperative risk evaluation. Illicit stimulant use has been associated with cardiovascular complications. This study investigates the impact of stimulant use and its interaction with surgery on cardiovascular complications in trauma patients.MethodsPatients were identified from the 2017 National Trauma Data Bank. Univariate and multivariate analyses were used to evaluate the effect of amphetamine and cocaine on mortality, myocardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Elsewhere, while the effect of opioids with polysubstance on mortality has not been explicitly reported, research has shown that results vary regarding the association between stimulant use and mortality (Hadjizacharia et al 2009 ; Neeki et al 2018 ). Satish et al investigated the association of amphetamine and cocaine separately on mortality, showing that cocaine reduced the odds of mortality among trauma patients, while amphetamine did not show any such association (Satish et al 2021 ). As highlighted, though, outcomes vary in the literature (Yeung et al 2013 ; Satish et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elsewhere, while the effect of opioids with polysubstance on mortality has not been explicitly reported, research has shown that results vary regarding the association between stimulant use and mortality (Hadjizacharia et al 2009 ; Neeki et al 2018 ). Satish et al investigated the association of amphetamine and cocaine separately on mortality, showing that cocaine reduced the odds of mortality among trauma patients, while amphetamine did not show any such association (Satish et al 2021 ). As highlighted, though, outcomes vary in the literature (Yeung et al 2013 ; Satish et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Satish et al investigated the association of amphetamine and cocaine separately on mortality, showing that cocaine reduced the odds of mortality among trauma patients, while amphetamine did not show any such association (Satish et al 2021 ). As highlighted, though, outcomes vary in the literature (Yeung et al 2013 ; Satish et al 2021 ). Our study stands unique, as it finds no association between the use of opioids and stimulants with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Another study [ 22 ] recently published used the national trauma database (NTDB) to evaluate the effect of amphetamine and cocaine on mortality. This study evaluated 317,688 patients who underwent urine drug screening in 2017.…”
Section: Discussionmentioning
confidence: 99%
“…However, cocaine and amphetamine have been associated with worsening postoperative complications, such as ventilator associated pneumonia or postoperative infection. 68 Cathinones Clinical signs and symptoms that need to be monitored during the perioperative period include agitation, hypertension, tachycardia, hyperreflexia, seizures, hyponatremia, rhabdomyolysis, and decreased renal function. 42 Like other sympathomimetics, cardiac side effects, including coronary vasospasm, myocardial ischemia, and hypertension, can be present.…”
Section: 4-methylenedioxymethamphetaminementioning
confidence: 99%
“…However, cocaine and amphetamine have been associated with worsening postoperative complications, such as ventilator associated pneumonia or postoperative infection. 68…”
Section: Perioperative Management Of Acute Psychostimulant Intoxicationmentioning
confidence: 99%